Establishing traceability for the measurement of scattering parameters in coaxial line systems. (25th January 2018) - Zeier, M; Hoffmann, J; Hürlimann, P; Rüfenacht, J; Stalder, D; Wollensack, M
Abstract: Scattering parameters are fundamental quantities in radio frequency and microwave metrology. Traceability to SI units for these measurements is established with the help of calculable standards. Progress has been made over recent years in characterizing these standards. Major steps forward have been achieved with advanced modelling of the entire standard, including connector interface and with the use of multivariate uncertainty evaluation, taking correlations fully into account. The improvements have led to more consistent, more accurate measurements.